Pengaruh Perbedaan Umpan Pada Alat Tangkap Sirib Anco (Lift Net) Terhadap Udang Lar (Macrobhium Lar) di Perairan Cijeruk Indah Kab Garut, Jawa Barat - M Kamal Abdal Nasser (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2026)
This study aimed to determine the effect of different bait types on the catch of larval shrimp (Macrobrachium lar) using a lift net and to determine the best bait type in the waters of Cijeruk Indah, Garut Regency, West Java. The method used in this study was an experimental method with nine replications. The independent variables in this study consisted of three types of bait: earthworms, fine rice husks, and pellets, while the dependent variable was the weight of the larval shrimp caught. The results showed that different bait types significantly affected the larval shrimp catch. Based on the total catch during the study, pellet bait yielded the highest yield, with a total weight of 2,316 grams. This was followed by fine rice husk bait with a total weight of 1,256 grams, and earthworm bait with the lowest yield, at 364 grams. Data analysis using ANOVA showed a significance value of 0.031 (p < 0.05), confirming a significant difference in catch responses between the three bait types. In conclusion, pellets are the most effective type of bait to use in the anco net fishing gear in catching larval shrimp at the research location.